Optimization of biogas-reforming conditions considering carbon formation, hydrogen production, and energy efficiencies. (15th February 2023) - Park, Min-Ju; Kim, Hak-Min; Gu, Yun-Jeong; Jeong, Dae-Woon
Abstract: Hydrogen production from biogas requires energy efficiency. This study systemically compared pure biogas reforming, CO2 -free biogas steam reforming, and biogas steam reforming. A comprehensive evaluation combining thermodynamic analysis, energy efficiency evaluation, and experimental validation was performed to compare the reaction types. Biogas steam reforming is the most attractive reforming reaction because it has the lowest SEC. In addition, the main parameters for the reaction conditions were investigated to optimize hydrogen production from biogas. The optimal conditions for the biogas steam reforming were determined as 750 °C and an H2 O/CH4 ratio of 1.5. Finally, the previously developed Ni–MgO–CeZrO2 catalyst was tested under the optimized reaction conditions. Consequently, the catalyst showed high catalytic performance and was maintained for 30 h, even at a high GHSV of 36 000 h −1 . This result implies that the optimized reaction condition derived by comparing the various indicators such as conversion of reactants, yield of products, energy consumption, and thermal efficiency is suitable for hydrogen production from biogas. Highlights: A comprehensive evaluation was performed to compare CO2 -free biogas and biogas reforming. The evaluation contained carbon formation, hydrogen production, and energy efficiencies. Biogas reforming without additional steam could not proceed because of carbon formation. Steam reforming of CO2 -free biogas and biogas showed maximum H2 production at a 1.5H2 O/CH4 ratio and 750 °C. Steam reforming of biogas was more energy-effective than that of CO2 -free biogas.